1970
DOI: 10.18388/abp.2013_2058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of leptin and leptin receptor genes in relation with production and reproduction traits in cattle.

Abstract: Leptin and leptin receptor genes are considered as production traits markers in dairy or beef cattle. The aim of this study was to verify the associations of polymorphisms in bovine LEP and LEPR genes with production and reproduction traits in Slovak Spotted and Pinzgau cows. Long-life production was evaluated: milk, protein, and fat yield and reproduction traits: age at first calving, calving interval, days open, and insemination interval. In total, 296 blood samples of Slovak Spotted and 85 hair roots sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 0 publications
0
28
0
7
Order By: Relevance
“…GH-TaqI, LEP-Sau3AI and MYF5-TaqI polymorphisms of the genes investigated had significant effects, especially on the 305-day milk yield of Holstein cows (Sahin and Akyuz, 2017, Kiyici et al , 2019). Trakovicka, (2013) reported that the SNP LEP/Sau3AI significantly influence milk, protein and fat yield (P<0.05) in cows. Similarly polymorphism with respect to leptin gene was highly significant with milk yield and milk composition traits in Polish Black and White cows (Polish Friesian) (Flisikowsk et al , 2004).…”
Section: Discussionmentioning
confidence: 97%
“…GH-TaqI, LEP-Sau3AI and MYF5-TaqI polymorphisms of the genes investigated had significant effects, especially on the 305-day milk yield of Holstein cows (Sahin and Akyuz, 2017, Kiyici et al , 2019). Trakovicka, (2013) reported that the SNP LEP/Sau3AI significantly influence milk, protein and fat yield (P<0.05) in cows. Similarly polymorphism with respect to leptin gene was highly significant with milk yield and milk composition traits in Polish Black and White cows (Polish Friesian) (Flisikowsk et al , 2004).…”
Section: Discussionmentioning
confidence: 97%
“…In another study, LEP/Sau3AI polymorphism and its effects on age at first calving, calving interval, days open, and insemination interval in Pinzgau and Slovak Spotted cows were RESEARCH ARTICLE monitored. It was noted that LEP/Sau3AI polymorphism significantly (P<0.01) affected the age at first calving in these cows (Trakovická et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Beberapa penelitian melaporkan secara khusus pada bagian promotor gen leptin sapi terdapat SNP berdasarkan GenBank: AJ571671 (Matteis et al 2012) dan AB070368 (Chung et al 2008). Polimorfisme gen leptin pada beberapa bangsa sapi dilaporkan memiliki asosiasi terhadap produksi karkas (Corva et al 2009), berat badan (Nobari et al 2010) dan produksi susu (Trakovická et al 2013). Studi tentang identifikasi SNP pada gen leptin sapi lokal di Indonesia masih sangat terbatas.…”
Section: Pendahuluanunclassified
“…Respon energi yang meningkat menyebabkan terjadinya penghancuran sel trigliserida dalam jaringan lemak sebagai upaya untuk melepaskan asam lemak bebas yang digunakan untuk proses oksidasi dalam metabolisme tubuh (Denver et al 2011 (Moussavi et al 2006), Sistani (Nobari et al 2010), Sarabi (Javanmard et al 2008), Golpayegani, Taleshi (Nahavandi et al 2010), Mazandarani, Dashtiyari (Javanmard et al 2005), Fries Holstein (Liefers et al 2002), lokal Irak (Hussain et al 2017), Slovak Spotted dan Pinzgau (Trakovická et al 2013). Polimorfisme pada bagian ekson 2 gen leptin (Lep/Kpn2I) dilaporkan terjadi pada sapi Golpayegani, Taleshi, Sarabi, Sistani, Fries Holstein dan Brown Swiss (Nassiry et al 2008), Iranian Holstein (Sadeghi et al 2008), Frieswal, Ongole, Sahiwal (Singh et al 2014) dan Polish Holstein-Friesian (Komisarek 2010;Moravcikova et al 2012), Hanwoo (Kong et al 2006), Jersey, Hariana, Sahiwal, Gir dan Nimari (Choudhary et al 2005).…”
Section: Struktur Gen Leptin Dan Mekanisme Kerja Hormon Leptinunclassified
See 1 more Smart Citation